Interventions to Expand Community Pharmacists' Scope of Practice - Zaynah Zureen Ali; Helen Skouteris; Stephanie Pirotta; Safeera Yasmeen Hussainy; Yi Ling Low; Danielle Mazza; Anisa Rojanapenkul Assifi (MDPI AG, 2024)
Background: The role of community pharmacists has evolved beyond the dispensing of medicines. The aim of this scoping review was to describe the interventions that expand the pharmacist's scope of practice within a community pharmacy setting and assess their effectiveness. Methods: We performed a scoping review to identify randomised controlled trials (RCTs), published worldwide from 2013 to 2024, which focused on interventions designed to expand pharmacists' scope of practice in the community. The review was undertaken in accordance with the Joanna Briggs Institute methodology for scoping reviews. To address the aim of this scoping review, the included RCTs were mapped to themes influenced by the Professional Practice Standards 2023 as developed by the Pharmaceutical Society of Australia: medication management, collaborative care and medication adherence. Results: Twelve studies demonstrated the potential to expand community pharmacists' scope of practice. Two RCTs resulted in no effect of the intervention. One RCT (conducted in Italy) led to an actual change to community pharmacists' scope of practice, with a statistically significant improvement in the proportion of patients with controlled asthma. Conclusions: On the whole, this scoping review synthesised the findings of peer-reviewed RCT studies that revealed expanding community pharmacists' scope of practice may result in improved patient outcomes, a reduced burden for the healthcare system, and greater productivity.